PENGARUH SUHU TUANG DAN FLUIDITAS ALUMINIUM (Al-9%Si) TERHADAP SIFAT MEKANIS DAN FISIS PADA PENGECORAN EVAPORATIF MODEL BIRMINGHAM - Budi Harjanto; Hirman Hirman (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2025)
The purposes of this study was: To know the difference influence of temperature variations on the rate of flow fluidity castings foundry results with the model evaporative Birmingham on Al-9% Si(1). To know the difference influence of temperature variations on the level of hardness cast evaporative casting model results in Birmingham Al-9% Si(2). To know the difference in the influence of temperature variations on the microstructure of casting Birmingham’s evaporative model in Al-9% Si. This research uses experimental methods. This study used Aluminum alloy ingots (Al-9% Si). Samples from this study is the result of the influence of temperature variations in the metal aluminum alloy castings against mechanical and physical properties. The number of samples for which there are 3 variations of temperature difference of the three 600°C, 700°C, 800°C. The results of this study were: (1)The measurement results obtained the conclusion that the fluidity between the different temperature variations of the highest value is at a temperature of 800°C and pour the fluidity of the lowest rate at a temperature of 600°C. (2)The mechanical properties of a form of violence each different test specimen temperature variation The greater the importance of the conclusion of the pour temperature hardness value to be dropped or small, because at the lowest temperature faster the freezing process that resulted in the material becomes harder. (3)The results of the microstructure obtained the conclusion that the grains are formed at the tip is greater than the base or middle, so the first freeze occurs on the tip of the middle and then later at the base.